America after Tocqueville : - Mitchell, Harvey (Cambridge University Press, 2002)
This study draws on Democracy in America to study the condition of democracy in the United States in our own time. Three aspects of Americanism inform Harvey Mitchell's book, and cannot be separated from Tocqueville's consideration of the three races. First, he addresses tensions in the United States between ideas of equality and a political system that tries to keep it within bounds. He turns to the relationship between this system and the dynamics of American capitalism. and he analyses the criteria for inclusion and exclusion in American life. Overall, he asks if Americans have surrendered to what Tocqueville called the materialization of life; if that compromise means their abandonment of their original spiritual quest; and, if they are on the way to a radical alienation from politics.